Perancangan Website Pembelajaran Bahasa Jawa Berbasis Metode Design Thinking - Mubarak, Fawwaz; Maulana, Reza (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
This research focuses on creating a user-friendly Javanese language learning website using the Design Thinking approach. The goal is to cater to the needs and preferences of young people comfortable with digital technology. The research follows a five-step process: empathize, define, ideate, prototype, and test. During the empathize phase, questionnaires were used to understand the learning needs of potential users. The define phase identified critical challenges faced by learners. In the ideate phase, brainstorming sessions generated various possible solutions. A website prototype was then designed using Figma and tested with users in the test phase. The System Usability Scale (SUS) was used to evaluate the prototype, and it received an average score of 83, which is considered excellent. This suggests that the designed website prototype effectively addresses user needs and preferences and has the potential to significantly boost motivation for learning the Javanese language.